A microstrip photonic crystal bandgap device with a switchable negative epsilon plasma element. Issue 12 (22nd September 2017) - Wang, B.; Lee, R.; Colon, R.; Cappelli, M. A.
Abstract: We present a microstrip photonic bandgap (PBG) device with a switchable plasma element integrated into the patterned ground plane. A pulsed laser plasma is generated in one of the PBG cavity structures creating a medium having an effective negative permittivity in the 8–10 GHz frequency range due to the high plasma density ne  = 10 17 cm −3 . The PBG structure consists of a linear array of seven cavities along the length of the microstrip manufactured by removing cylindrical portions of copper in the ground plane. The plasma is produced in the central cavity of the PBG array and recombines over times of several microseconds allowing for the characterization of the microstrip transmission over a range of plasma density. The results confirm a switchable transmission due to plasma interactions with the electromagnetic field within the PBG structure.